Interactions Between Bovine Respiratory Syncytial Virus and Cattle: Aspects of Pathogenesis and Immunity - Lariane da Silva Barcelos; Alexandra K. Ford; Matheus Iuri Frühauf; Nadalin Yandra Botton; Geferson Fischer; Mayara Fernanda Maggioli (Viruses, 2024)
Bovine respiratory syncytial virus (BRSV) is a major respiratory pathogen in cattle and is relevant to the livestock industry worldwide. BRSV is most severe in young calves and is often associated with stressful management events. The disease is responsible for economic losses due to lower productivity, morbidity, mortality, and prevention and treatment costs. As members of the same genus, bovine and human RSV share a high degree of homology and are similar in terms of their genomes, transmission, clinical signs, and epidemiology. This overlap presents an opportunity for One Health approaches and translational studies, with dual benefits; however, there is still a relative lack of studies focused on BRSV, and the continued search for improved prophylaxis highlights the need for a deeper understanding of its immunological features. BRSV employs different host-immunity-escaping mechanisms that interfere with effective long-term memory responses to current vaccines and natural infections. This review presents an updated description of BRSV’s immunity processes, such as the PRRs and signaling pathways involved in BRSV infection, aspects of its pathogeny, and the evading mechanisms developed by the virus to thwart the immune response.